Review of Dimitris D. Arvanitakis, Η Αγωγή του πολίτη: Η γαλλική παρουσία στο Ιόνιο (1797-1799) και το έθνος των Ελλήνων : [Educating the citizen: The French presence in the Ionian Sea (1797–1799) and the Greek nation] - Pagratis, Gerassimos D. (Historein, 2023)
Review of Dimitris D. Arvanitakis, Η αγωγή του πολίτη: Η γαλλική παρουσία στο Ιόνιο (1797–1799) και το έθνος των Ελλήνων [Educating the citizen: The French presence in the Ionian Sea (1797–1799) and the Greek nation]. Iraklio: Crete University Press, 2020. 782 pp.